KOMPETISI NET INTEREST MARGIN (NIM) PERBANKAN INDONESIA : BANK KONVENSIONAL DAN SYARIAH - Warno Warno; Dessy Noor Farida (Jurnal Dinamika Ekonomi & Bisnis, 2017)
Banking will be able to speed up the Indonesian economy if NIM is low, from OJK data show that high above 5 percent when compared with NIM in overseas banking which is below 4 percent, in Indonesia there are conventional bank and syariah bank and BPRS with various characteristics different, but between banks there is a strong competition to win in the market. The amount of NIM is influenced by several variables: Operating Cost, Risk Aversion, Size, Implicit interest payment, Specialization.Samples were taken from all companies listed at Otorias Jasa Keuangan (OJK) in 2005-2016, as many as 106 Conventional Banks and 11 Syariah Banks and 169 Sharia Rural Banks were processed using software stata. From the result of the research indicate that for the NIM variable between BUS, BU and BPRS the smallest is at BPRSS equal to -0,4919037 and biggest at BUS equal to 15, from the data indicate that at BPRS better and duck on BUS, while Competition between the three shows the smallest is at the BPRS of 0.0101014 and the largest in the SRB of 1, from the data shows that the BPRS competition is the worst, also the best, from the variable Operating Cost between the three smallest in the BU of 0.0016908 and the largest in the BPRS of 1.837655, from the data shows that best on and BU badest in BPRS.From the output view of the Stata model summary the magnitude of adjusted R square is 0.2580, this means that 25% of NIM variation can be explained by the variation of the five independent variables while the remainder (100-25 = 75) is explained by causes other than the model and value R square is 0.2580, this means 25% NIM is influenced by independent variables simultaneously, and NIM is induced by partially independent variables because the significance value of the five variables below 0.05 consists of SIZE, Specialization, Risk Aversion, Implist Interest Pyment and Operating cost, output stata also shows the value of F arithmetic is 171 and F table is 0.22 the results explain the influence of independent variables to the dependent variable.Based on the three main variables, namely NIM, competition and operating cost indicate that the most vulnerable to lose in market mechanism is BPRS followed by BUS and most strong BU, because NIM in overseas banking tends to be small, but in BUS and BPRS has the advantage of being able to get NIM which is very low but can also be the highest because their profits can be large and small match the benefits obtained by customers / parties who are invited to cooperation, if the profit of customers high then the NIM will be high and vice versa.Limitations in this study is the normality test shows research data that has a lot of data variations that can affect the conclusion and the latter with a small value adjusted R square shows there are other variables that are not examined affect the NIM and Competitio.